(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Infection control remains a critical aspect of healthcare delivery, ensuring patient safety and minimizing the risk of healthcare-associated infections (HAIs). As healthcare settings evolve and new challenges emerge, it is imperative for healthcare professionals to continually advance their infection control practices. This article provides a comprehensive overview of key strategies for enhancing infection control in various healthcare settings. Drawing upon evidence-based practices and guidelines, the article examines proactive measures, effective protocols, and emerging technologies that healthcare professionals can leverage to mitigate the spread of infectious agents. Additionally, it addresses the importance of interdisciplinary collaboration, education, and ongoing training in fostering a culture of infection prevention and control within healthcare organizations.